Factors Associated with Anxiety and Depression among Elderly Living in Old Age Homes - Suwal, Ratee Pakwan; Upadhyay, Bijen; Chalise, Hom Nath (KMC Journal, 2024)
Anxiety and depression are the most common psychological problems in older people. The older people living in older person’s residential care facilities are more vulnerable. This study aims to explore anxiety and depression and associated factors of older people staying in care facilities in Nepal. This is a descriptive cross-sectional quantitative study. A total of 216 older people were recruited from Old Age Homes (OAH) of Kathmandu Valley. Anxiety was assessed using Beck Anxiety Scale and depression was assessed using the GDS-15 scale. Statistical software SPSS 23.0 was used for data entry and analysis. The mean of anxiety was 13.23±6.84. The prevalence of anxiety disorder in the study population was 8.8 % and depression disorder was 74.5%. Results show gender, marital status, religion, type of previous family, chronic illness, stress, and type of living facilities were significantly associated with anxiety. Similarly, that being male, having chronic diseases, comorbidities, and feelings of stress are related to depression. The difference was statistically significant (p<0.05). Depression and anxiety were also significantly positively correlated (r=0.232, p< 0.01). Elderly people living in care facilities had slightly low levels of anxiety and high depression. Government and residential care facilities should be aware to provide appropriate support, care, and early psychological care during the intervention for the elderly so that it will help to control anxiety depression and other health problems so that older people enjoy the quality of life.